Influence the cationic substitution in AgGaGe₃Se₈ on the electro-optical, IR optical and nonlinear properties - Krymus, A.S.; Myronchuk, G.L.; Parasyuk, O.V.; Kityk, I.V.; Piasecki, M. (Functional Materials, 2017)
In present article we present results of detailed study of the possibility adapting AgGaGe3Se8 single crystal properties to desired requirements by investigate the influence of the different cationic substitution on the physical properties: optical, nonlinear optical (NLO) - Second Harmonic Generation (SHG) and temperature dependent photoconductivity. We report results obtained for modified crystals based on AgGaGe₃Se₈ by cationic substitution of the elements belong to first - (Ag-Cu), third (Ga-In), and fourth (Ge-Sn) groups of the periodic system. For the convincing observation the effects of various impurities and compare results with obtained for virgin AgGaGe₃Se₈ crystal was conducted replacing at 5 mol. % one element by another.